Neuronal damage and shortening of lifespan in C. elegans by peritoneal dialysis fluid: Protection by glyoxalase-1 - Schlotterer, Andrea; Pfisterer, Friederike; Kukudov, Georgi; Heckmann, Britta; Henriquez, Daniel; Morath, Christian; Krämer, Bernhard; Hammes, Hans-Peter; Schwenger, Vedat; Morcos, Michael (Biomedical reports, 2018)
Glucose and glucose degradation products (GDPs), contained in peritoneal dialysis (PD) fluids, contribute to the formation of advanced glycation end-products (AGEs). Local damaging effects, resulting in functional impairment of the peritoneal membrane, are well studied. It is also supposed that detoxification of AGE precursors by glyoxalase-1 (GLO1) has beneficial effects on GDP-mediated toxicity. The aim of the current study was to analyze systemic detrimental effects of PD fluids and their prevention by glyoxlase-1. Wild-type and GLO1-overexpressing Caenorhabditis elegans (C. elegans) were cultivated in the presence of low- and high-GDP PD fluids containing 1.5 or 4% glucose. Lifespan, neuronal integrity and neuronal functions were subsequently studied. The higher concentrations of glucose and GDP content resulted in a decrease of maximum lifespan by 2 (P<0.01) and 9 days (P<0.001), respectively. Exposure to low- and high-GDP fluids caused reduction of neuronal integrity by 34 (P<0.05) and 41% (P<0.05). Cultivation of animals in the presence of low-GDP fluid containing 4% glucose caused significant impairment of neuronal function, reducing relative and absolute head motility by 58.5 (P<0.01) and 56.7% (P<0.01), respectively; and relative and absolute tail motility by 55.1 (P<0.05) and 55.0% (P<0.05), respectively. Taken together, GLO1 overexpression protected from glucose-induced lifespan reduction, neurostructural damage and neurofunctional damage under low-GDP-conditions. In conclusion, both glucose and GDP content in PD fluids have systemic impact on the lifespan and neuronal integrity of C. elegans. Detoxification of reactive metabolites by GLO1 overexpression was sufficient to protect lifespan, neuronal integrity and neuronal function in a low-GDP environment. These data emphasize the relevance of the GLO1 detoxifying pathway as a potential therapeutic target in the treatment of reactive metabolite-mediated pathologies.